The association between cardiac intensive care unit mechanical ventilation volumes and in-hospital mortality. Issue 7 (19th July 2021) - Nandiwada, Shiva; Islam, Sunjidatul; Jentzer, Jacob C; Miller, P Elliott; Fordyce, Christopher B; Lawler, Patrick; Alviar, Carlos L; Sun, Louise Y; Dover, Douglas C; Lopes, Renato D; Kaul, Padma; van Diepen, Sean
Abstract: Aims: The incidence of respiratory failure and use of invasive or non-invasive mechanical ventilation (MV) in the cardiac intensive care units (CICUs) is increasing. While institutional MV volumes are associated with reduced mortality in medical and surgical ICUs, this volume–mortality relationship has not been characterized in the CICU. Methods and results: National population-based data were used to identify patients admitted to CICUs (2005–2015) requiring MV in Canada. CICUs were categorized into low (≤100), intermediate (101–300), and high (>300) volume centres based on spline knots identified in the association between annual MV volume and mortality. Outcomes of interest included all-cause in-hospital mortality, the proportion of patients requiring prolonged MV (>96 h) and CICU length of stay (LOS). Among 47 173 CICU admissions requiring MV, 89.5% (42 200) required invasive MV. The median annual CICU MV volume was 43 (inter-hospital range 1–490). Compared to low-volume centres (35.9%), in-hospital mortality was lower in intermediate [29.2%, adjusted odds ratio (aOR) 0.84, 95% confidence interval (CI) 0.72–0.97, P = 0.019] and high-volume (18.2%; aOR 0.82, 95% CI 0.66–1.02, P = 0.076) centres. Prolonged MV was higher in low-volume (29.2%) compared to high-volume (14.8%, aOR 0.70, 95% CI 0.55–0.89, P = 0.003) and intermediate-volume (23.0%, aOR 0.85, 95% CI 0.68–1.06, P = 0.14] centres. Mortality and prolonged MV were lower in percutaneous coronary intervention (PCI)-capable and academic centres, but a shorter CICU LOS was observed only in subgroup of PCI-capable intermediate- and high-volume hospitals. Conclusions: In a national dataset, we observed that higher CICU MV volumes were associated with lower incidence of in-hospital mortality, prolonged MV, and CICU LOS. Our data highlight the need for minimum MV volume benchmarks for CICUs caring for patients with respiratory failure. Graphical Abstract: